Depth Estimation of the Aquifer Using Geoelectric Technique and It′s Comparison with Drilling Result in Pekuncen Village, Jatilawang District, Banyumas Regency - Septiawan Nurul Handika; Muhammad Sehah (Pusat Survei Geologi, 2020)
Pekuncen Village, Jatilawang District is one of the villages in Banyumas Regency which often experiences drought in the dry season. Exploration to obtain the groundwater sources needs to be done, especially to estimate the depth of the aquifer. The chosen exploration method was resistivity geoelectric using vertical sounding technique. Resistivity data acquisition is carried out on 3 trajectories with the length of the 1st and 3rd trajectories are 200 m, and the 2nd trajectory is 240 m. The sounding point on the 2nd trajectory was drilled, where rock samples were taken at every 5 m depth. The rock samples obtained were correlated with the resistivity data interpretation results, including the type and thickness of each depth. The aquifer in the research area consisted of two parts, namely unconfined aquifer and confined aquifer. The unconfined aquifer at the first sounding point is located at 6.80 – 34.38 m depth, the second sounding point at 7.00 – 28.89 m depth, and the third sounding point at 4.39 – 31.39 m depth. Then the confined aquifer at the first sounding point is located at less than 48.24 m depth, the second sounding point at less than 47.22 m depth, and the third sounding point at less than 47.36 m depth. The correlation between the resistivity data interpretation results at the second sounding point and the drill log data shows a slight difference in rock types and thickness. The difference of the rock types due to the drilling data interpretation results which divides the sand in the confined aquifers into fine, medium, and coarse grained sand. The difference of confined aquifer depth after being correlated is less than 2 m depth.Keywords: Aquifer, geoelectric survey, resistivity data, drill, Pekuncen, Banyumas.